Division of labour within the visual system: fact or fiction? Which kind of evidence is appropriate to clarify this debate - Stöttinger, Elisabeth; Soder, Kathrin; Pfusterschmied, Jürgen; Wagner, Herbert; Perner, Josef (Experimental brain research, 2010)
The perception versus action hypothesis of Goodale and Milner (Trends Neurosci 15:20-25, 1992) and Milner and Goodale (The visual brain in action. Oxford University Press, Oxford, 1995) postulated two different pathways within the visual system—one for action and one for perception. With the help of pictorial illusions, evidence for this dissociation was found in various studies. There is an ongoing debate, however, as to whether or not this evidence is biased by methodological issues. Indeed, relevant and decisive data can come only from those studies that (1) match conditions appropriately with respect to task demands, (2) use illusions that do not provide any potential obstacles for the hand, (3) do not risk that grasping is either memory driven (when the target is not visible) or online corrected (due to a direct comparison of the grip aperture with the size of the target object), (4) do not confound differences between perception and action conditions with differences in visual feedback, and (5) correct for differences in response functions between grasping and perception. In following all these points outlined above we found support for the perception versus action hypothesis: grip aperture follows actual size independent of illusory effects, while perceived length as indicated by finger-thumb span clearly was subject to the illusion.